1995
DOI: 10.1074/jbc.270.30.18036
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the S3 Subsite Specificity of Cathepsin B

Abstract: Five synthetic substrates containing different amino acid residues at the P3 position (acetyl-X-Arg-Arg-AMC, where X is Gly, Glu, Arg, Val, and Tyr and where AMC represents 7-amindo-4-methylcoumarin) were used to investigate the S3 subsite specificity of cathepsin B. At pH 6.0, the specificity constant, kcat/Km, for tripeptide substrate hydrolysis was observed to increase in the order Glu < Gly < Arg < Val < Tyr. Molecular modeling studies of substrates containing a P3 Glu, Arg, or Tyr covalently bound as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
19
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 26 publications
3
19
0
Order By: Relevance
“…The efficient cleavage of P 2 ϭ Lys substrates can be attributed to the presence of Glu 205 in the P 2 pocket (papain numbering), which can mediate the charge of the basic residues via salt bridging (63)(64)(65). Cathepsin B demonstrated specificity for Lys, Leu, and Pro in the P 3 position, which is consistent with literature reports (59,66).…”
Section: Resultssupporting
confidence: 80%
“…The efficient cleavage of P 2 ϭ Lys substrates can be attributed to the presence of Glu 205 in the P 2 pocket (papain numbering), which can mediate the charge of the basic residues via salt bridging (63)(64)(65). Cathepsin B demonstrated specificity for Lys, Leu, and Pro in the P 3 position, which is consistent with literature reports (59,66).…”
Section: Resultssupporting
confidence: 80%
“…In addition, both cathepsins L and B have been activated in the presence of Brij 35 (4 -6), while cathepsin S has been activated in the presence of Triton X-100 (4). Sometimes cathepsins are even assayed in the absence of detergents (7)(8)(9). Although the properties and utilization of detergents in biochemistry have been reviewed extensively (10 -12), their influence on enzyme catalysis has not yet been fully examined.…”
mentioning
confidence: 98%
“…Essentially no effect is seen for the generic cysteine protease substrate Z-FR-Amc or for the amidated form of the quenched fluorescence substrate Abz-FRF(4NO # )A. These compounds are neither typical exonor endo-peptidase substrates since, although they are short (thus mimicking exopeptidase substrates), no terminal charge is present, and in the case of Z-FR-Amc, the leaving group does not reach into the S # subsite [39]. Correct orientation of the loop is critical for exopeptidase action, as demonstrated by the almost complete lack of activity of the D22A\H110A mutant with the Abz-FRF(4NO # )A exopeptidase substrate, which is an excellent wild-type cathepsin B substrate.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, cathepsin B was shown to have relatively low (20-fold) specificity in the P # subsite. Cathepsin B has been shown to have a similar level of specificity in the P $ subsite [39]. As a general principle, the major specificity determinant of the papain family is an extremely high selectivity for large hydrophobic residues in P # , for example 2700-and 12 000-fold higher activity for Leu compared with Arg in the case of cathepsins S and cathepsin K respectively [40,41], and similar patterns for cathepsin L and cathepsin L2 (cathepsin V) [42].…”
Section: Discussionmentioning
confidence: 99%